2017
DOI: 10.7575/aiac.ijalel.v.7n.1p.113
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Collaborative Writing on Iranian EFL Learners' Task Achievement in Writing and Their Perception

Abstract: Collaborative writing has gained interest in the last decade; however, as stated by Shin, Lidster and Sabraw (2016) more research is required to delve into various aspects of this multifarious class activity. This true experimental research examined the effect of writing collaboratively on task achievement of Iranian EFL learners in writing. Oxford Placement Test was given to 60 language learners in the city of Kashmar, Iran,  as the test of homogeneity. Considering +/-1 standard deviation of the mean score, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…As a result, he points out that learners became more committed in completing their writing. In a study conducted by Khodabakhshzadeh and Samadi (2017), most participants found collaborative writing was very effective as it enhanced their motivation. Jalili and Shahrokhi (2017) also found that collaborative groups had significantly lower writing anxiety rates than the individual group.…”
Section: The Effects Of Collaborative Writingmentioning
confidence: 99%
“…As a result, he points out that learners became more committed in completing their writing. In a study conducted by Khodabakhshzadeh and Samadi (2017), most participants found collaborative writing was very effective as it enhanced their motivation. Jalili and Shahrokhi (2017) also found that collaborative groups had significantly lower writing anxiety rates than the individual group.…”
Section: The Effects Of Collaborative Writingmentioning
confidence: 99%
“…Khodabakhshzadeh and Samadi [35] examined the effect of CW on task achievement of Iranian EFL learners. e findings revealed that the collaborative group outperformed the individual group.…”
Section: Related Empirical Studiesmentioning
confidence: 99%
“…Moreover, no investigation has focused on the elements of writing fluency, accuracy, and complexity for the Iranian EFL learners yet. Reviewing the research on learners' perceptions of CW, several studies have reported students' evaluations of CW as favourable such as [28,30,34,35]. However, the number of studies exploring learners' attitudes toward grouping and collaboration with different patterns of scaffolding is scant.…”
Section: Related Empirical Studiesmentioning
confidence: 99%
“…It is supported by Bosley (1989), students' responsibility on each steps of collaborative writing process reaches a higher quality of writing. Besides, collaborative writing provides an opportunity to generate ideas and feedback for students error and monitor them in group working (Shehadeh, Khodabakhshzadeh and Samadi, 2017). Those studies found that collaborative writing reach students' improvement on students' critical thinking and helped them in developing their writing by considering some writing aspects include organization and vocabulary, mechanics, content but not in achieving of writings' accuracy.…”
Section: Introductionmentioning
confidence: 99%